Factors associated with the burden of family caregivers of patients with mental disorders: a cross-sectional study - Ana Lúcia Rezende Souza (BMC Psychiatry, 2017)
Abstract Background Caregivers are responsible for the home care of family members with mental-health disorders often experience changes in their life that can generate stress and burden. The aim of this study was to identify factors associated with the burden of caregivers of family members with mental disorders. Methods This cross-sectional study was conducted with a non-probability sample of family caregivers, whose patients attended a community services program, the Psychosocial Care Centers, in three cities in the southwest region of Goiás State, Central Brazil. Data collection took place from June 2014 to June 2015. The participants were 281 caregivers who completed a sociodemographic questionnaire and the Zarit Burden Interview (ZBI). Bivariate analyses (t test, analysis of variance, and Pearson correlation) were performed, and variables with values of p < 0.10 and gender were included in a multiple-linear regression model. Values of p < 0.05 were considered significant. Results The caregivers were mostly female and parents of the patients, were married, with low education, and of low income. The mean ZBI score was 27.66. The factors independently associated with caregivers’ burden were depression, being over 60 years of age, receiving no help with caregiving, recent patient crisis, contact days, and having other family members needing care. Conclusions This study identified factors that deserve the attention of community services and can guide programs, such as family psycho-education groups, which may help to minimize or prevent the effects of burden on family caregivers responsible for patients’ home care.